Implementation of Good Corporate Governance (GCG) and ESG in State Owned Enterprises in Indonesia - Aji Ardana (Jurnal Global Ilmiah, 2026)
Good Corporate Governance (GCG) and Environmental, Social, and Governance (ESG) are increasingly important concepts in the development of modern corporate law, particularly within State-Owned Enterprises (SOEs) in Indonesia. The implementation of GCG aims to establish companies that are transparent, accountable, responsible, independent, and fair, while ESG emphasizes corporate sustainability through environmental, social, and governance dimensions. In practice, several Indonesian SOEs continue to face various legal and governance issues, such as corruption, conflicts of interest, weak supervision, and suboptimal implementation of corporate sustainability principles. This study aims to analyze the implementation of Good Corporate Governance and ESG in Indonesian SOEs and to identify the challenges encountered in their application. This research employs a normative legal research method using statutory, conceptual, and case approaches. The primary legal materials include Law Number 19 of 2003 concerning State-Owned Enterprises, Law Number 40 of 2007 concerning Limited Liability Companies, as well as various regulations related to corporate governance and ESG. The findings indicate that the implementation of GCG and ESG in Indonesian SOEs has shown progress, particularly in improving corporate transparency, strengthening supervisory functions, and adopting corporate sustainability programs. However, implementation still faces several challenges, including political intervention, weak independence of corporate organs, and the lack of comprehensive ESG regulations and effective supervision. Therefore, stronger regulatory frameworks, enhanced corporate accountability, and more effective oversight mechanisms are required to achieve sound and sustainable governance within Indonesian SOEs.